2009
DOI: 10.1542/peds.2008-0603
|View full text |Cite
|
Sign up to set email alerts
|

Sports Injuries to High School Athletes With Disabilities

Abstract: This adapted sports program is a reasonably safe activity for children with disabilities. Nonetheless, findings have important implications for prevention. The preparticipation medical examination may be an excellent opportunity to create special guidelines, particularly for athletes with autism and seizure history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 25 publications
3
19
0
3
Order By: Relevance
“…18 Little research exists on sports injuries to young athletes with disabilities. 19 In a study in high school athletes with disabilities, 38 injuries were reported (2 per 1000 athletes); soccer (3.7 per 1000) had the highest rate of injury, including mostly abrasions and contusions. At highest risk for injury were athletes with autism, history of seizures, and starters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Little research exists on sports injuries to young athletes with disabilities. 19 In a study in high school athletes with disabilities, 38 injuries were reported (2 per 1000 athletes); soccer (3.7 per 1000) had the highest rate of injury, including mostly abrasions and contusions. At highest risk for injury were athletes with autism, history of seizures, and starters.…”
Section: Discussionmentioning
confidence: 99%
“…This information may provide the physicians and trainers the rationale to stratify a protocol for preparticipation medical examination of these athletes, to create special guidelines, particularly for athletes with autism and seizure history. 19 Moreover, little is known about sport nutritional problems and requirements of athletes with physical disabilities. Since proper nutrition is important for both performance and injury healing, learning about the nutritional areas in which athletes with disabilities are deficient may assist professionals in educating them.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little evidences support this hypothesis. [17][18][19][20][21][22] Most studies demonstrate the rate of injuries of athletes with disability comparable to able-bodied athletes.…”
Section: Scmentioning
confidence: 99%
“…Estudios previos también han puesto de manifiesto que el riesgo de lesiones puede complicarse al existir una discapacidad previa (Ramirez et al 2009). Esto es de interés particular debido a que las lesiones y molestias relacionadas con el deporte representan serias limitaciones para la actividad física que pueden conducir a los deportistas a interrumpir sus programas de entrenamiento (Mahy et al 2010).…”
Section: Discussionunclassified